Комунікативно-прагматичні параметри рецензійного тексту - Левчук, Ірина; Levchuk, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто особливості рецензійного тексту в системі наукової комунікації, визначено його основні ознаки, зосереджено увагу на комунікативно-прагматичних параметрах. З’ясовано типологічне та індивідуально- авторське у вживанні різноманітних засобів лексико-семантичного та синтаксичного рівнів для створення потрібного прагматичного ефекту. This article deals with the peculiarities of the edition notice abstract within the system of scientific communication. The main features of the edition notice abstract have been defined. Extensive attention has been devoted to communicative and pragmatic parameters. It is demonstrated that the edition notice abstract constitutes a peripheral genre of scientific style with a high level of standardization on all levels of text construction and invariant structure. It has been pointed out that the edition notice abstract harmoniously combines information for readers regarding the contents of a scientific publication with an analysis of its principal assertions and potentially with an evaluation of the work. On this basis, It is possible to identify this genre’s two main functions – informational and evaluative. In addition to this, it is possible to distinguish secondary functions relating to the promotion of the paper under analysis, a preconditioning of criteria for the evaluation of the paper, and the creation of new verbal forms of scientific ‘etiquette’ as well as the refinement of existing ones. Typological and individual author-specific features in terms of the usage of various lexical, grammatical, semantic and syntactic means for creating a pragmatic effect have been identified.
Communicative and Pragmatic Parameters of the Edition Notice Abstract
Keywords: наукова комунікація; рецензія; комунікативно-прагматичні параметри; оцінна інформація; scientific communication; edition notice abstract; communicative and pragmatic aspects; evaluative information